Diagnosis Of Dengue Infection Using Metabolome Analysis (Biomarkers Profiling) - Noor, Nurul Shahfiza (2014)
Dengue is a major health and pressing threat to Malaysia with increasing atypical manifestations. These including encephalopathy, hepatic failure, renal failure, myocarditis and rhabdomyolysis which.have been attributed chiefly to metabolic alterations. Therefore, the metabolomics approach was used to investigate for metabolite candidates that potentially could be utilized as an indicator for dengue disease; leads to dengue severity. In this study, attempt was made to determine the metabolic response associate with dengue infection by means of 11-1 NMR-based metabolomic spectrometry. We also explored the differences in gender infected with dengue disease. Fifty-two patients diagnosed with dengue fever at Penang General Hospital and fourty-three healthy individuals were recruited in this study. The mid-stream urine collected was analyzed with 11-1 NMR spectroscopy, followed by chemometric multivariate analysis. Two types of pattern recognitions were employed, namely, Principle Component Analysis (PCA) and Orthogonal Partial Least SquareDiscriminant Analysis (OPLS-DA). NMR signals which highlighted in the OPLS-DA S-plot were further selected and identified using Human Metabolome Database (HMDB), Chenornx Profiler and from published literature.